Speech by Y.A.B. Dr Lim Chong Eu at the Dinner given by Barisan Nasional in honour of Y.A.B. Perdana Menteri on Sunday 10th October 1976 at 8.00 p.m. - Lim, Chong Eu (1976)

(untitled)
On behalf of the Barisan Nasional,State of Penang I welcome Y.A.B. Perdana Menteri to our function tonight as the National President of Barisan Nasional as well as our national leader.